THE EFFECT OF CORN SILK ETHANOL EXTRACT (Zea mays L.) ON THE BLOOD GLUCOSE LEVELS AND HISTOPATHOLOGY OF PANCREAS IN ALLOXAN-INDUCED MICE - Nessa, Nessa; Ifmaily; Wahyu Putri, Sri (SITAWA : Jurnal Farmasi Sains dan Obat Tradisional, 2025)
Diabetes Mellitus is a metabolic disorder that occurs because pancreatic cells produce insulin in small amounts. The purpose of this study was to determine the effect of giving corn silk (Stigma maydis) to alloxan-induced mice to determine the effective dose of corn silk extract that can reduce blood glucose levels in hyperglycemic mice and histopathological features. This research is an experimental type that uses 24 male white mice as experimental animals, divided into 6 groups and each group consists of 4 mice consisting of negative control, positive control, dose variation 100mg/kgBW, 200mg/kgBW, 400mg/kgBW and the comparison group (Glibenclamide 0.65mg/kgBW). The inducer used was alloxan 150 mg/kg bw. Alloxan induction was carried out for 3 days and then the test preparation was given until the 17th day. Mice's blood was taken through the lateral tail vein to see blood sugar levels. Based on the results of measuring the blood glucose levels of mice on day 17, the average value of blood glucose levels was negative control (86.25 mg/dl), positive control (223 mg/dl), dose 100 mg/kgbb (109.75 mg /dl), dose 200 mg/kgbb (103.5 mg/dl), dose 400 mg/kgbb (92.5 mg/dl), glibenclamide 0.65mg/kgbb (95 mg/dl). Based on the results of statistical data analysis, two-way ANOVA showed significantly different results (p<0.05). The results of reducing blood glucose levels that were closest to the negative control were shown by corn silk extract at a dose of 400 mg/kgbb, while histopathological observations of the pancreas after administration of ethanol extract of corn silk at a dose of 200 mg/kgbb showed the best healing in the islets of Langerhans.